Transition to full-fledged inflation targeting : a proposed programme for implementation by the Central Bank of Nigeria - Ojo, Michael O.; Central Bank of Nigeria, Research Department (Abuja, Nigeria Central Bank of Nigeria, 2013)
The paper addresses the issues that could constrain the smooth take off of inflation targeting in Nigeria and proffer solutions on how the Central Bank of Nigeria can successfully transit from its current monetary targeting framework into one of inflation targeting.
Includes bibliographical references.
oif 16/05/17
Ref.
Keywords: Inflation; Nigeria